Study guides

☆☆

Q: When the sum of a number plus 3 is squared it is 9 more than the sum of the number plus 2 when squared.?

Write your answer...

Submit

Related questions

When the sum of a number plus 3 is squared, it is 11 more than the sum of the number plus 2 when squared.

2

3

4

4

2

4

a number equals 2

If you mean: (x+3) squared = (x+2) squared +11 Then the value of x works out as 3

if it is not this . -3<x<-2 < or equal

Are you asking me to tell you the answer? Because its easy and simple .

2

The sum of a number plus 3 to the square root of 9 to the sum of 2 would equal -2. This is a math problem.

[(x+3)^2] - [(x+2)^2] = 13 ==> 2x = 8 ==> x = 4. the number is 4!

If you mean: (x+3)^2 = (x+2)^2 +13 Then the value of the number x works out as 4

More. 4 squared = 16 4.1 squared = 16.81 any number greater than 4 when squared is larger

2 x n(squared) + 2

7 Squared is 49. 10 plus 49 is 59.

(x + 3)2 = (x + 2)2 + 9 x2 + 6x + 9 = x2 + 4x + 4 + 9 2x = 4 x = 2

This is equivalent to (x + 3)2 = (x + 2)2 + 9. Multiplied out this is x2 + 6x + 9 = x2 + 4x + 4 + 9. Deduct x2 + 4x + 9 from each side giving 2x = 4 So x = 2 Check: (2 + 3) squared = 25 which is 9 more than (2 + 2) squared = 16.

(x + 3)(x + 3) = (x + 2)(x + 2) + 11 x^2 + 6x + 9 = X^2 + 4x + 15 6x + 9 = 4x + 15 2x + 9 = 15 2x = 6 x = 3 Check it. 3 + 3 squared (36) is 11 more than 3 + 2 squared (25) It checks.

Let's translate that to algebra: (x+3)2 = 13+(x+2)2 I'll leave the rest to you.

No because then it will have more than two factors

The number is 4 (4+3) * (4+3) = 49 (4+2) * (4+2) = 36 49 - 36 = 13

The original number is 10 because: 10 squared = 10+90